Impacto dos procedimentos cirúrgicos múltiplos concomitantes no risco de infecção de sítio cirúrgico - Silvio Augusto Corsini Menicucci (2009)
It is an opened historical cohort where 190.443 surgical patients were supported in order to study the surgical site infection (SSI) and its risk factors. The studied potential risk factors for SSI were: the degree of contamination of the surgical wound according to the National Research Council, the anesthetic surgical risk according to the American Society of Anesthesiologists criteria, the length in minutes of the surgery longer than the percentile 75 of the study population, the number of simultaneous surgical procedures which the patient was submitted, the type of surgery (elective/urgency/trauma) and after discharge contact. The univariated and multivariated analyses were accomplished according to the technique of logistic regression. The adequacy of the model was evaluated by the Hosmer-Lemeshow test. It was used a significance level of 0,05 and confidence interval of 95%. Most of the patients was submitted to only one surgical procedure (98%) and demonstrated the anesthetic surgical risk according to the American Society of Anesthesiologists (ASA) in its lower level, 1 (82,5%). The elective surgeries corresponded to 65,5% of the procedures being those with potentially contaminated wound the most common (61,2%) followed by clean surgeries (31,2%) and the SSI occurred in 3,9% of the cases. When performing the univariated analysis, all the potential risk factors demonstrated connection with the ISS. The multivariated analysis sustained as risk factor the time of the surgery over 100 minutes (OR 1,70 and p=0,001 ), the number of surgical procedures which the patient was submitted: 2 (OR 1,43 and p=0,001) and 3 or 4 (OR 1,91 and p=0,049), the potential of contamination of the surgical wound: potentially contaminated (OR 1,70 and p=0,001), contaminated (OR 2,13 and p=0,001) and infected (OR 2,81 and p=0,001) and the ASA classification: 2 (OR 1,36 and p=0,001), 3 (OR 3,20 and p= 0,001) and 4 or 5 (OR 2,50 and p=0,001) and after discharge contact (OR 2,19 and p=0,001) as risk factors for the surgical site infection.